Isolation, characterization and therapeutic potential of a novel furanoid diterpene lactone from Hedychium spicatum rhizomes: Insights into antioxidant, anxiolytic, and circadian rhythm modulating properties - Alok Pratap Singh; Rajeev Kumar Sharma; Ashok Behera; Jay Ballabh Kandpal; Havagiray Chitme; Pankaj Pant (Elsevier, 2024)
Background: Hedychium spicatum rhizomes is widely used in ayurvedic medicine and traditional medicine systems around the Himalayas. Purpose: Standardization of Hedychium spicatum rhizome SCFE extract by Identification, Isolation, characterization, and screening of pharmacological activity of phytoconstituents. Study design: Supercritical fluid extraction, column chromatography, spectroscopic analysis, in-silico, and in-vivo study of compound 1 (3-((E) -2-((1S,8aR)-3,5,5,8a-tetramethyl-4-oxo-1,4,4a,5,6,7,8,8a-octahydro-naphthalen-1-yl) vinyl) furan-2(5H)-one). Methods: A supercritical fluid extract was prepared and further purified to obtain a novel Furanoid diterpene lactone compound 1 (3-((E) -2-((1S,8aR)-3,5,5,8a-tetramethyl-4-oxo-1,4,4a,5,6,7,8,8a-octahydro-naphthalen-1-yl) vinyl) furan-2(5H)-one). It was characterised using IR, LC-ESI/MS, 1H, 13C NMR, 2D NMR-COSY, NOESY, HMBC, and HSQC and thin-layer chromatography. Compound was tested for anxiolytic activity using various animal behavioural model included elevated maze plus test, light and dark box test, social interaction, actophotometer test, rotarod test. Results: The compound gives a false Dragendorff's test in favour of the presence of lactone. HPLC profiling was done using DAD using 30 % v/v of o-phosphoric acid (0.1 % v/v) in water and 70 % v/v of acetonitrile (ACN) in the mobile phase. Compound 1 having significant anxiolytic effect tested in animal behavioural model ****p < 0.0001 diazepam as standard. Conclusion: Free radical scavenging activity suggested that compound 1 has good potential as an antioxidant, having IC50 values of 75.62 µg and 96.556 µg using DPPH and ABTS inhibition assays. ADMET prediction suggested that compound 1 follows Lipinski's rules of five, absorbed through the intestine, and penetrates the blood-brain barrier and CNS. In-silico studies, suggested that compound 1 has an affinity to bind with GABA, melatonin 1, and glutamate receptor 5 and In-vivo study suggest compound 1 will be a good candidate as anxiolytic agent. It can be used as a promising natural remedy for oxidative stress, mental health issues, and sleep-related disorders, warranting further exploration and clinical investigation.